A framework for educational data warehouse (EDW) architecture using business intelligence (BI) technologies - Azwa, Abdul Aziz; Hasni, Hassan; Julaily Aida, Jusoh (Little Lion Scientific, 2014)
Business Intelligence (BI) is the process of getting the right information to the right decision makers at the right time and in the right format. It is a platform that supports analysis, reporting and decision making. Educational Business Intelligence (EduBI) architecture utilizes BI technologies to integrate various sources of academic data into a single repository (Educational Data Warehouse – EDW). BI is a useful tool since it reinforces the process of performance and analysis evaluation that is required within all levels of educational environment. Nowadays, there are various BI products ranging from simple reporting technologies to sophisticated BI platforms. Selection of a BI tool deemed appropriate for a particular task may turn out to be difficult; hence careful considerations must be made in the selection process. This paper proposed an EDW architecture that employs the integration of proprietary and open source BI tools.